Big data analysis as a tool for assessing professionalization of computer sports - Ermakov, A.V.; Skarzhinskaya, E.N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate the criteria and assess the level of professionalization of the sport "Computer Sports" using big data analysis tools. Methods and structure of the study. The analysis of organizational and economic characteristics of eSports tournaments of various levels (Tier 1 and Tier 2) was carried out using a Python script and library script for this study. A statistical analysis of the numerical variables of the Tier 1 and Tier 2 teams by years (2011-2022) is also presented. Results and conclusions. The signs of professionalization of the studied eSports discipline were revealed, which indicated the need to build scientific and methodological support for sports training.